Effect of Nitrogen Application Timing on Yield Components, Fodder, Grain, and Oil Yields of Brassica Cultivars. Issue 8 (28th April 2017) - Arif, Muhammad; Tariq, Muhammad; Jan, Mohammed; Akbar, Habib; Mian, Ishaq; Sajid, Muhammad
ABSTRACT: The dual-purpose use of Brassica cultivars means cutting or grazing the crop as fodder and then letting it to re-grow and produce grain with little or no yield penalty. A field experiment was conducted in randomized complete block design with split plot arrangement with three replications. Three Brassica cultivars, three nitrogen application timing, and cutting treatments were included in the experiment. The findings indicated that Brassica cultivar Abasin-95 produced higher fresh and dry fodder yields, seeds pod −1, seed, biological, and oil yields. However, NIFA Raya resulted in a higher number of pods and branches plant −1 . Likewise, fresh and dry fodder yields were higher with nitrogen (N) application all at sowing. Nitrogen applied in two splits resulted in a higher number of pods plant −1 and grain yield. Cutting suppressed all parameters except 1000 grain weight. Uncut plots produced significantly higher branches plant −1, pods plant −1, seeds pod −1, seed, biological, and oil yields than cut plots.